Capability, Opportunity, dan Rationalization pada Kecurangan Laporan Keuangan dengan Income Tax Rate sebagai Efek Moderasi (Studi Empiris Perusahaan Non Keuangan yang Terdaftar di BEI 2020-2022) - Triyani, Nur; Yusrianti, Hasni; Thamrin, Kemas Muhammad Husni (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the influence and analyze the influence of capabilities, opportunities, and rationalization on the condition of financial statements and the role of income tax rates as a moderating variable in non-financial companies listed on the Indonesia Stock Exchange in 2020–2022 as the population in this study. The data in this study consisted of 207 observations determined using the purposive sampling method. Data collection uses documentation techniques collected from annual financial reports and annual reports. The analysis technique used is Moderated Regression Analysis (MRA) with Eviews. Based on the results of the regression test, capabilities and opportunities influence the condition of financial statements, while rationalization cannot influence the condition of financial statements. The results of the moderation regression show that the income tax rate is able to moderate opportunity, while other income tax rates are not able to moderate it. The practical implications of this research can provide information for stakeholders in decision making.